2015
DOI: 10.1007/s00170-015-7508-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutions of grain size and micro-hardness during chip formation and machined surface generation for Ti-6Al-4V in high-speed machining

Abstract: Machined surface with ultrafine grained microstructure can be obtained through severe plastic deformation in high-speed machining (HSM) process. The aim of this paper is to investigate the evolution of grain size and microhardness during HSM of Ti-6Al-4V alloy using the finite element method (FEM) and user subroutine VUSDFLD of Abaqus/Explicit. Firstly, a FE model to simulate the cutting process of Ti-6Al-4V is proposed. The proposed cutting simulation model is verified by high-speed machining experiments in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(27 citation statements)
references
References 28 publications
(40 reference statements)
0
25
0
2
Order By: Relevance
“…In recent years, various modelling attemps has met with the need of reliable measurements to either discriminate and/or validate models [37]. The use of post-mortem analysis such as chip morphology and SEM analysis [57,67,17,61,60] remains the most common approach. Force components measurement in real time trough Kistler dynamometer is also very popular and has become almost dogmatic in machining research [53,33].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various modelling attemps has met with the need of reliable measurements to either discriminate and/or validate models [37]. The use of post-mortem analysis such as chip morphology and SEM analysis [57,67,17,61,60] remains the most common approach. Force components measurement in real time trough Kistler dynamometer is also very popular and has become almost dogmatic in machining research [53,33].…”
Section: Introductionmentioning
confidence: 99%
“…During the micro-cutting Ti-6Al-4V process, the workpiece in the annealed condition was adopted, and its microstructure mainly consisted of equiaxed α phase grains and a small quantity of β phase. On the basis of Wang et al [ 19 ], the effect of the β phase can be ignored because of its small volume fraction in Ti-6Al-4V alloy. Therefore, only equiaxed α phase grains were used in the present study, and the grain size was 3.4 μm × 2.95 μm.…”
Section: Methodsmentioning
confidence: 99%
“…It is found that the subsurface damage layer is principally accommodated by dislocation evolution and slip bands within alpha phase grains [10]. In particular, on the basic of Liu et al [28], the effect of beta-titanium on subsurface plastic deformation can be ignored in cutting simulation process due to the low volume fraction of beta phase, which is not more than 8%. Thus, it is reasonable to assume that only alpha grains were considered in present study, and indicating that the subsurface zone was composed of hexagonal close-packed (HCP) structural crystals.…”
Section: Subsurface Damage Of Titanium Alloy In Cutting Processmentioning
confidence: 99%